1996
DOI: 10.1089/end.1996.10.443
|View full text |Cite
|
Sign up to set email alerts
|

Electromotive Administration of Intravesical Lidocaine in Patients with Interstitial Cystitis

Abstract: Six patients with long-standing interstitial cystitis (IC) were treated with intravesical electromotive drug-assisted (EMDA) therapy using lidocaine (1.5%) and 1:100,000 epinephrine in aqueous solution. A stainless-steel silver-coated anode placed through an 18F Foley catheter was positioned in the urinary bladder, and a 5 x 10-cm dispersion electrode (cathode) was placed on the suprapubic skin, which was well lubricated with conductive jelly. The two electrodes were connected to a pulsed DC generator, and ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Except for mild symptoms associated with application of electrical current (tingling and erythema), no major side e¡ects have been observed [Gurpinar et al, 1996a;Riedl et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for mild symptoms associated with application of electrical current (tingling and erythema), no major side e¡ects have been observed [Gurpinar et al, 1996a;Riedl et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, iontophoretic and electrophoretic drug delivery (electromotive drug administration, EMDA) have been utilized to allow for deep penetration of substances like lidocaine, dyes, mitomycin C, dexamethasone, and epinephrine into the bladder wall [Lugnani et al, 1993;Gurpinar et al, 1996a;Di Stasi et al, 1997;]. In experimental studies, dyes were found in the upper layers of the bladder muscle after EMDA therapy [Gurpinar et al, 1996b].…”
Section: Introductionmentioning
confidence: 99%
“…EMDA represents a new and attractive method for intravesical administration of several drugs [25, 26, 27]. This technique is based on several electrokinetic phenomena, mainly iontophoresis.…”
Section: Discussionmentioning
confidence: 99%
“…Positive outcomes of bladder capacity, voiding frequency, and pain were also reported using EMDA lidocaine followed by cystodistension. [15][16][17] Although studies using intravesical EMDA have shown improved analgesia when used as an anesthetic for bladder procedures such as hydrodistension, capsaicin instillation, and bladder biopsies, absorption kinetic studies have not been published. 18,19 Alkalinization of intravesical lidocaine with sodium bicarbonate was first described in 1979 by Higson et al 20 They administered 40 mL of 1% lidocaine with 40 mL of 8.4% sodium bicarbonate, held in the bladder for 30 minutes, to 20 subjects with urinary frequency, urgency, and incontinence who were diagnosed with detrusor instability at that time.…”
Section: Evaluation Of Literaturementioning
confidence: 99%